Power electronics: applications in renewable energy sources edp y energia renovable (Revista de Investigaciones Universidad del Quindío, 2014)
IIn recent years the use of electricity has increased considerably, but the use of non-renewable energy sources have a negative environmental impact, making it necessary to use new technologies for renewable energy and clean energy like wind energy. This article is a review of the most recent technologies developed for the management of energy from renewable sources and the use of power electronic systems.
Keywords: Power systems; energy conversion; generators; control